Resettlement of Koreans and their Role in Development of Agriculture of Primorskaya Oblast in the Latter Half of the XIX - the Early of the XX Century - Tsareva, Natalia Aleksandrovna; Aleshchenko, Valentina Nickolaevna (International Journal of Economics and Financial Issues, 2015)
In the article on the basis of archival material and historical sources attempt to study questions of resettlement of Koreans to the south of the Far East of Russia in the latter half of XIX - the early of the XX century, the reason of migration and adaptation of the Korean immigrants on the new location is made. Continuous resettlement process from Korea to Primorskaya oblast (at the present time – Primorsky Krai) is considered, its dynamics and numerical indicators. Vast majority of the Korean immigrants were engaged in agriculture. Features of farming by the Korean immigrants are investigated, considering use of the agricultural experience which is saved up in Korea, the country with similar climatic, soil conditions. The question of the farming, the Korean agricultural stock, specifics of cultivation of traditional Korean grain crops are studied. One of the directions of agriculture of Koreans – silkworm breeding, its organization and results of production is investigated. It is noted that introduction to an agricultural turn of those lands which the Russian peasants considered unsuitable for agriculture; bed-grown way of processing of the land; variable system of landing plants; receiving more big crops of all species of agricultural plants, than the Russian peasants had; distribution of new agricultural plants among the population of Primorskaya oblast promoted effective farming and its development. The question of borrowing Russian peasants’ practices by the Korean immigrants– cultivation of new species of plants – oats, wheat, a rye – for sale, use of agricultural stock, horses is studied. The mutual exchange of the saved-up experience and knowledge in different branches of agriculture allowed reclaiming the South of the Far East of Russia effectively. Keywords: Koreans migration, Primorsky Krai, agriculture, arable farming, silkworm breeding. JEL Classifications: M55, Q12